The autobiography and other writings - Franklin, Benjamin, 1706-1790.; Lemisch, Jesse, 1936- (New York : Signet Classic, 2001)
Collection of material that reveals an extraordinary person, Benjamin Franklin.
Includes bibliographical references (p. [341]-343).
Keywords: Franklin, Benjamin, -- 1706-1790.; Statesmen -- United States -- Biography; Scientists -- United States -- Biography; Printers -- United States -- Biography; United States -- Politics and government -- To 1775.; United States -- Politics and government -- 1775-1783.; Franklin, Benjamin, -- 1706-1790.; Political science; Printers; Scientists; Statesmen; United States; To 1783; Biography